2000
DOI: 10.1054/bjoc.1999.1086
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards prophylactic surgery and effects of genetic counselling in families with BRCA mutations

Abstract: Mutation analysis of the BRCA1 and BRCA2 genes has become widely available to hereditary breast and ovarian cancer families (HBOC) or breast-cancer-only families (HBC) in North America and Europe. To date, hundreds of these families have been identified with BRCA mutations and the majority has received counselling regarding the test results. Follow-up care of mutation carriers has focused on cancer surveillance and surgical options (Burke et al, 1997). However, little is known about the impact carrier status h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 18 publications
3
41
0
3
Order By: Relevance
“…This is in agreement with findings from a study conducted among Austrian women at high risk in which about three in ten (29%) considered preventive mastectomy. 17 About half (49.1%) of respondents in urban areas who were willing to accept preventive bilateral mastectomy had a higher knowledge, higher educational attainment, self-perceived risk compared with those in rural areas. This may partly be explained by better knowledge, awareness and access to information on breast cancer including its risk factors among respondents in urban areas compared to rural areas.…”
Section: Discussionmentioning
confidence: 98%
“…This is in agreement with findings from a study conducted among Austrian women at high risk in which about three in ten (29%) considered preventive mastectomy. 17 About half (49.1%) of respondents in urban areas who were willing to accept preventive bilateral mastectomy had a higher knowledge, higher educational attainment, self-perceived risk compared with those in rural areas. This may partly be explained by better knowledge, awareness and access to information on breast cancer including its risk factors among respondents in urban areas compared to rural areas.…”
Section: Discussionmentioning
confidence: 98%
“…Cases with weak (1C), moderate (2C), or strong (3C) staining intensities were considered to have an elevated expression of IGF-I and/or IGF-IR and were considered 'positive'. BRCA 1/2 status was determined as described previously (Wagner et al 2000).…”
Section: Immunostaining Quantificationmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] The acceptance of prophylactic mastectomy varies significantly among countries. A study from The Netherlands reported an uptake rate of 51% for BRCA1 and BRCA2 mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Several international studies have been conducted to measure the interest in and uptake rate of prophylactic mastectomy in high-risk women. [7][8][9][10][11][12][13] Rates of uptake among BRCA1 and BRCA2 mutation carriers vary from 3% 13 to 51%. 11 The popularity of prophylactic mastectomy seems to be dependent on the country, suggesting marked cultural variation.…”
mentioning
confidence: 99%